EVALUATION OF LOCAL RECLAMATION DATA FOR SUSTAINIBILITY INFRASTUCTURE FACILITIES (CASE STUDY OF KLAWAS ZONE AND SUBAN ZONE IN POST COAL MINING AIR LAYU TANJUNG ENIM) - Gumanti, Johnnedy; Sutriyono, Edy; Salni, Salni; Harnani, Harnani (BIOVALENTIA: Biological Research Journal, 2018)
This study identifies and analyzes the biophysical and environmental aspects of the environment, potentials and constraints, and then evaluates the post-mining reclamation land use that will be used for Other Use Areas (APL), the Residential Infrastructure Facility. Based on the Mining Closure Plan (RPT) on the utilization of former coal mine land at Air Laya Tanjung Enim, Klawas reclamation land use plan for Resettlement Facility and Zoning Infrastructures (Zone 2) while Suban reclamation land use plan for Productive Research area. Analysis in this research are scoring, SWOT and map overlay such as area function analysis and land suitability analysis based on physical condition of existing land. The result of this research is land suitability level for Residential Infrastructure Facility in Klawas, suitable land equal to 12% or 38 ha while 98% unfit or 258,7 ha from total area of 277,8 ha. Terms of land suitability in Klawas research area including Marginal (S3) with total scores of 80. where climate condition support with average temperature 24oC and rainfall 23,93 - 27,87 mm / day, slope of flat slope approaching water level river 0 - 3%, complex geological structure there are anticline in the form of fault and fracture, soil type Alluvial and Latosol, there are many aquifer with shallow depth to medium, there is vulnerability of geological disaster in the form of mass movement of soil / rock, flood, erosion and radiation exposure TENORM of moderate intensity. The results of land use evaluation for the Klawas reclamation area are more suitable for Freshwater Fishery Cultivation area than for Residential Infrastructure Facility area. Land tenure rate for Residential Infrastructure Facility in Suban, suitable land equal to 76 % or 237 ha while unsuitable 24% or 105 ha of total area of 342 ha. Conditions of land suitability in Suban's research area include Match (S2) with a total scores of 130. Climatic conditions support the average air temperature of 24Â°C and rainfall of 23.93 - 27.87 mm / day, the slope of flat slope is 3 - 8% there is no anticline structure in the form of fault, Andosol and Podsolic soil types, there is a shallow shallow depth of aquifer, no geological disaster vulnerability and low intensity TENORM radiation exposure. The results of the land-use evaluation for the Suban reclamation area are more suitable for the Residential Infrastructure area rather than for Productive Research area.